PELAKSANAAN MANAJEMEN MADRASAH PADA PONDOK PESANTREN DARUD DAKWAH WAL IRSYAD (DDI) PATTOJO KABUPATEN SOPPENG - Achruh, Andi; Iqbal, Muhammad (Universitas Islam Negeri Alauddin Makassar, 2020)
This study aims to analyze the implementation of madrasah management at the Darud Dakwah Wal Irsyad (DDI) Pattojo Islamic Boarding School, Soppeng Regency. In the process of collecting data, the author uses the method of observation and interviews with madrasah principals, madrasah teachers, madrasah staff, village heads, religious leaders, community leaders and youth leaders. Management is a way that is done so that other people can work and are willing to do something well and maximally and can use the best time possible. Furthermore, if the word management is associated with the word madrasah, then madrasah management is a way that is done professionally to raise and improve the madrasah by controlling and supervising all activities carried out. Making all elements in the madrasah work properly and optimally. Related to the management and development of madrasah management, namely by means of planning (planning), organizing (organizing), leadership (leading) and supervision (controlling). The implementation of madrasah management at the Darud Dakwah Wal Irsyad Pattojo boarding school in Soppeng Regency has been implemented and implemented quite well. So that the Darud Dakwah Wal Irsyad Pattojo boarding school, Soppeng Regency, still exists today and is still in great demand by various people. As for the role of the Darud Dakwah Wal Irsyad Pattojo boarding school, Soppeng Regency, after being studied from various perspectives, namely as a unifying element of society, development in the field of religion and development in the field of education. The author sees that the management of the Darud Dakwah Wal Irsyad Pattojo boarding school in Soppeng Regency has opportunities and challenges. With the development of sophisticated technology, all information systems and technology can become major capital in the development of these madrasas. However, there is a lack of human resources capable of adapting to these developments, so it still requires special training related to this management.